Chronic Hepatic Venous Ischemia Secondary to Venous Outflow Insufficiency Causes Chronic Rejection in Pediatric Liver Transplant Recipients - Magd A. Kotb; Mohamed ELGharib; Hesham Abd ElKader; Magda El-Monayeri; Ahmed El-Hennawy; Sherif Kaddah; Hend Abd El Baky; Nazira A. Abdalla; Radwa A. Shamma; Iman Ali Abdel Aziz (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Venous ischemia in a closed compartment results in congestion, impeded blood supply, cell death and a cascade of events that involves immune system to remove cellular debris. Aim of the Work: To report our experience with chronic hepatic venous ischemia post liver transplant. Methods: We describe 3 girls and 4 boys with chronic hepatic venous ischemia secondary to chronic hepatic venous outflow insufficiency (CHVOI) post-liver transplant as confirmed by magnetic resonance venography (MRV) and by interventional radiograms. Results: The mean age at transplantation was 6.75 years. Following transplant, within 8.5±1.7 months they presented with progressive jaundice, ascites and hepatosplenomegaly. Imaging showed features consistent of CHVOI. The percutaneous liver biopsy revealed a picture of predominant chronic rejection and not of venous congestion. They improved clinically following hepatic venous dilation but not with change of type or dose of immuno-suppression. The venous- outflow tightness recurred with unsustained clinical improvement. Two children had stent placement. All others had irreversible progressive course developing end-stage liver disease. All were indicated for re-transplant. Of them 5 died awaiting re-transplant. Conclusions: Chronic rejection among our studied children was due to insufficient intraoperative hepatic venous-outflow structural construction. CHVOI in children leads to graft loss and presents as chronic rejection. CHVOI should be ruled out in any child presenting with chronic rejection. Very generous hepatic venous outflow surgical construction technique should be planned, individualized and secured during liver transplant procedure. Stent placement is life-saving. Changes of immunosuppression medications is ineffective in CHVOI.